A Review of Jos Plateau 2010 Inter-Religious Conflict and Its Conflict Resolution Mechanism - Adedeji, Bethel Oluwatosin (African Journal of Stability and Development (AJSD), 2018)
Jos, the capital of Plateau State, was a region known for peace, until the eruption of violence in 2001 which claimed the lives of many Christians and Muslims. The involvement of these two religious groups resulted in the 2010 Interreligious conflict. Many intervention efforts were launched by Plateau State government, including the creation of Plateau State Peace Building Agency, to create and facilitate the growth of peaceful coexistence between the inhabitants of the state. Also, the government has provided sustainable security measures that have prevented fresh outbreak of conflict. This study, therefore, examines the causes of the conflict, assesses the conflict resolution mechanisms and suggests ways of preventing reoccurrence of conflict in Plateau State. Relevant literature dealing with conflict and religious conflicts alongside the history and causes of the 2010 Jos Inter-religious conflict was reviewed. The social identity and human needs theories are used to understand why people behave the way they do especially with regard to unmet human needs, which trigger behavioural change. The study adopted descriptive research design, using both primary and secondary data collection. Primary data were gathered from direct and indirect parties to the 2010 conflict with the use of semi-structured open-ended interview. Secondary data were obtained from journals, books, newspapers and the internet. Data collected from the primary source were carefully examined and analysed using content analysis. The data collected indicated that crises in the region were caused by the failure of the Nigerian government to address issues of unemployment and security of lives and properties. The result showed that the conflicts that have occurred in Jos were caused by politics and not religion. The findings further established that the government has not fully addressed the causes of the Jos crisis and this failure could lead to reoccurrence of conflict in the region. In view of this, for the government to make a change, provisions should be made for access to employment and education in Jos, Plateau State. Also, non-governmental organisations (NGOs) should strive to monitor ongoing projects to achieve the objective for which they are commissioned, notably attainment of peace in Jos City and Plateau State in entirety.